Upcycle: As A New Preference in the Art of Climate Change - Centaury Harjani (IJCAS (International Journal of Creative and Arts Studies), 2020)
The most common inspiration used in the art of climate change is global warming. Indeed, the greenhouse effect that leads to a global temperature rise is the cause of global warming. This effect occurs due to increasing levels of carbon released into the air. Upon this, an artist needs to reduce carbon emissions for the sake of a better environment. One of the effective ways is by using the principles of environmentally friendly (low-carbon emissions) artwork. The way that can be chosen is upcycling in the making of an artwork. Upcycled is the upgraded version of Recycling. Upcycle will help reduce carbon emissions by utilizing old goods as materials to create an artwork. Upcycle does not use new materials, and it uses the method of material processing with a short phase compared to recycling. The contemporary art of climate change raises many issues on global warming as its inspiration. Therefore, it should pay attention to the material used in the making of environmentally friendly artwork. This paper will discuss the upcycle as a preference to produce that artwork. Practice-based research methods and literature studies are used in this study. This research will also discuss creative strategies in upcycling deadstock to become part of climate change contemporary artwork. The preliminary result from this study is that the upcycle will be optimal when combined with the principle of zero-waste. Upcycle: Preferensi Baru dalam Seni Perubahan Iklim ABSTRAK Inspirasi yang paling banyak digunakan pada seni perubahan iklim adalah pemanasan global. Sesungguhnya, efek rumah kaca adalah penyebab utama adanya peningkatan suhu secara global sehingga terjadi pemanasan global. Efek ini terjadi disebabkan oleh peningkatan jumlah karbon yang dilepaskan ke udara. Karena itu, seniman perlu berpartisipasi mengurangi jumlah gas buang karbon demi lingkungan yang lebih baik. Satu cara efektif yang dapat dilakukan adalah menggunakan prinsip karya seni ramah lingkungan yang tingkat gas buang karbonnya rendah. Cara yang dapat dipilih adalah melakukan upcycle dalam pembuatan karya seni. Upcylce ini adalah peningkatan versi dari Recycle. Upcycle akan membantu mengurangi gas buang karbon dengan memanfaatkan barang-barang lama sebagai bahan baku pada proses pembuatan karya seni. Upcycle tidak menggunakan material baru dan memiliki proses pengolahan material yang lebih pendek jika dibandingkan dengan metode recycle. Seni kontemporer terkait perubahan iklim mengangkat banyak isu mengenai pemanasan global. Karena itu, seni ini perlu memperhatikan bahan baku yang digunakan untuk memperoleh karya seni yang ramah lingkungan. Makalah ini akan membahas upcycle sebagai preferensi untuk menghasilkan karya seni tersebut. Metode penelitian berbasis praktik dan studi literatur digunakan dalam penelitian ini. Penelitian ini juga akan membahas strategi kreatif dalam melakukan upcycling bahan baku deadstock karya seni kontemporer perubahan iklim. Kesimpulan awal dari penelitian ini, penggunaan upcycle akan lebih optimal jika dipadukan dengan prinsip zero-waste.